1998
DOI: 10.1007/pl00005192
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant effect of the calcitonin gene-related peptide (CGRP) on the nonpregnant and pregnant rat uterus. Comparison with vascular tissue

Abstract: To explore the role of calcitonin gene-related peptide (CGRP) in rat pregnancy, we determined the density of myometrial CGRP-encoded nerve fibre terminals and examined, in an organ bath, the relaxant effect of the peptide on uterine strips near parturition. Comparisons were made with the uterus and aorta of nonpregnant rats. In the myometrium, CGRP immunoreactive nerve fibers were abundant in nonpregnant rats and scarce at the parturient stage. In the aorta there was no variation in the density of CGRP fibres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The NPY-containing nerves are also distributed intimately with the epithelial cells of the monkey ejaculatory duct which have few ultrastructural features indicating a positive secretory activity (Yokoyama, 1989). CGRP was considered a marker of sensory nerves (Yamada et al, 1977;Ngassapa et al, 1998) and had numerous biological functions like relaxing non vascular smooth musculature (Anouar et al, 1998;Yousufzai and Abdel-Latif, 1998;Hislop et al, 1998) and modulating sensory signals (Häppola and Lakomy, 1989;Csillik et al, 1993) and together to SP were involved in the control of the pain sensation (Santicioli et al, 1988). Rare SP-and CGRP-positive nerve fibres were found in alpaca, thus confirming the results in the camel epididymis (Saleh et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The NPY-containing nerves are also distributed intimately with the epithelial cells of the monkey ejaculatory duct which have few ultrastructural features indicating a positive secretory activity (Yokoyama, 1989). CGRP was considered a marker of sensory nerves (Yamada et al, 1977;Ngassapa et al, 1998) and had numerous biological functions like relaxing non vascular smooth musculature (Anouar et al, 1998;Yousufzai and Abdel-Latif, 1998;Hislop et al, 1998) and modulating sensory signals (Häppola and Lakomy, 1989;Csillik et al, 1993) and together to SP were involved in the control of the pain sensation (Santicioli et al, 1988). Rare SP-and CGRP-positive nerve fibres were found in alpaca, thus confirming the results in the camel epididymis (Saleh et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…3A) inhibited the CGRP-induced vascular relaxation effects in pregnant uterine arteries partially but significantly. Studies of Anouar et al [36] suggested that the relaxant effects of CGRP are abolished by inhibitors of nitric oxide synthase in rat aortas but not in the uterus. Recent studies in mouse uteri demonstrated that the relaxation of the myometrium by CGRP is independent of nitric oxide synthase activity [37].…”
Section: Discussionmentioning
confidence: 98%
“…We observed a noticeable reduction in the expression of the CGRP (calcitonin gene-related peptide)-receptor transcript at term. According to Anouar et al [20] and to Dong et al [21], the loss of CGRP response at term could contribute to initiation of rat and human labor. An up-regulation of a calmodulin-dependent phosphodiesterase (PDE-1) was observed at term as it has been clearly established in human term myometrium [22].…”
Section: Contraction-associated Genesmentioning
confidence: 97%